Toeholds and Takeovers. - Bulow, J; Huang, M; Klemperer, P (1999)
Toeholds have an enormous impact in 'common-value' takeover battles, such as those between two financial bidders. This contrasts with the small impact of a toehold in a 'private-value' auction. The authors' results are consistent with empirical findings that a toehold helps a buyer win an auction, sometimes very cheaply. A controlling minority shareholder may, therefore, be effectively immune to outside offers. A target may benefit by requiring 'best and final' sealed-bid offers or by selling a cheap toehold or options to a 'white Knight.' The authors' analysis extends to regulators selling 'stranded assets,' creditors bidding in bankruptcy auctions, and so forth.